New Technique of Beads Removal by Modifying Alligator Forceps - Khayat , Farhad Jalil (Diyala Journal of Medicine, 2019)
Background: Removal of spherical object like beads from tracheobronchial tree is very difficult due to their round and slippery nature which makes their grasp impossible by ordinary forceps during rigid bronchoscopy (RG.BR). Aim: The aim of this study was to improve new forceps to achieve an easy and swift technique to remove beads from tracheobronchial tree. Patients and method: This study was conducted at Rizgari teaching and Erbil emergency hospitals between 1984 and 2006 and involved 75 children with bead inhalation. The diagnosis was confirmed by viewing the typical shadow of beads which could be seen on plain chest x-ray accompanied by different initial clinical signs and symptoms such as choking, cough, respiratory distress, stridor, cyanosis and fever. All beads were removed by a modified minute forceps. Result: From the total of 75 patients, 49 patients were males and 26 were females. Forty eight beads were in right main bronchus and 15 were in left main bronchus, while the other 12 beads were in trachea and carina. Most of the patients (85.3%) attended hospital immediately. Conclusion: Despite improvements in technology, there is still no appropriate removal forceps for tracheobronchial tree beads. The new improvised grasping forceps showed excellent success and such improvement can be adopted by the relevant companies to develop a special forceps for this purpose.